The peopling of the Americas: new insights from genetic studies - Schurr, Theodore (Henry Stewart Talks, 2007)
Anthropological background, Clovis first model, Pleistocene overkill hypothesis, Megafauna extinction models, Cactus Hill, Topper site, Monte Verde, New coastal routes into the New World, Was Clovis first?, Two different founding populations colonized the Americas, Linguistic evidence, Genetic background, mtDNA lineages in native Americans, mtDNA haplogroup frequencies in Siberia and the Americas, Population history of Amerindian haplogroups, Haplogroup X in North and Central America, Prehistoric European migration to North America, History and diversification of circumarctic peoples, Ancient vs. modern population diversity, Colonization of the Caribbean, Y chromosome haplogroup frequencies in the Americas, Y chromosome haplogroup frequencies in native Siberians, Y chromosome SNP haplotype network, Migration models based on Y chromosome data
Archived at 2021/02/25